The position of the unrepresented accused in the subordinate courts in Malaysia / Gurdial Singh Nijar - Gurdial Singh, Nijar (1978)
This is a formulative or exploratory study which examines the relative position of the represented and the unrepresented accused persons before the subordinate courts in Malaysia. The aim of this study is primarily to ascertain whether the unrepresented accused is disadvantaged when compared with his represented counterpart and, if so, to what extent. The premise on which this study proceeds is that if reasons extraneous to the guilt - determining process affect the proper outcome of a case, then a proper functioning of the rule of law in the criminal area is in question. The State is then obliged to correct this, and at the very least minimise the impact of these factors, if the adversary trial system is to be preserved. Many countries, no less Malaysia, accept that an unrepresented accused is disadvantaged and have instituted schemes to provide counsel to an indigent accused. Financial limitations, however, have resulted in schemes of a limited nature. In Malaysia Legal aid in the criminal area is confined to the provision of counsel to advance mitigation pleas on behalf of an accused person after he has been found guilty. This study then also traces the impact of counsel at every stage of the trial process viz., plea, trial and sentence, to ascertain whether scarce resources are being rationally applied. The choice of the subordinate courts as the focus of this study is justified on three grounds, namely, first, the bulk of the criminal cases are heard by these courts, and especially the Magistrates Courts, secondly, the subordinate court cases, in particular those from the Magistrates Courts affect a far greater number of people and thirdly, the greatest number of convictions are recorded in the subordinate courts, and in particular the Magistrates Courts. Further, although the High Court hears the most serious cases, the subordinate courts, nonetheless, also try cases with potentially serious consequences. Datq in respect of four Magistrates Courts and three Sessions Courts over a two year period (1972 - 1973) were collected and analysed primarily from court records, supplemented by interviews of accused persons and observations in the courts. The main study was in respect of all criminal cases registered between January to July 1973 at the Magistrate's Court, Kuala Lumpur (Total sample: 309). To obtain a representative result the courts chosen were located in urban, semi-urban and semi-rural areas. The study examines, first, the level of representation at each stage of the trial process namely, plea, trial and sentence, and relates the representation both to the seriousness of the offence (in terms of the penalty imposable), and the nature of the charge. An assessment is also made as to whether the location of the court affects representation level. Some tenative reasons for the high level of unrepresentation recorded are proferred. Legal representation in relation to the plea recorded is also examined. Data are also analysed to ascertain whether the retention of counsel results in a change of pleas, especially from guilty to not guilty. The relationship between representation and findings in cases where the accused persons plead not guilty and proceed to trial of their case is also traced. The study also examines the impact of representation on final stage of the trial process, namely the imposition of the sentence. Some of the variables which affect outcome are identified and are controlled to make more reliable inferences possible. A special evaluation is made of the role of counsel for mitigation purposes. The actual position of the accused person in court is also examined. The lay-out of the court, court procedures and mannerisms are evaluated to ascertain whether they create problems for the unrepresented accused in I articulating his case. Finally the study describes the various legal aid systems which have evolved to provide counsel to an indigent accused. The relative merits of these models are traced and the main features of a model delivery system are attempted. A brief account of novel funding sources for this model delivery system is also presented. Where appropriate results of similar studies carried out elsewhere, for example, Australia, U.S.A., and England are set out for comparative purposes. Recourse is also made to reports of committees in these countries looking into the question of the provision of legal services to indigent accused persons.